Neonatal pigs are susceptible to experimental Zika virus infection - Joseph Darbellay; Kenneth Lai; Shawn Babiuk; Yohannes Berhane; Aruna Ambagala; Colette Wheler; Donald Wilson; Stewart Walker; Andrew Potter; Matthew Gilmour; David Safronetz; Volker Gerdts; et al. (Emerging Microbes and Infections, 2017)
Emerging Microbes & Infections (2017) 6, e6; doi:10.1038/emi.2016.133; published online 15 February 2017